Application of Cooperative Learning Models of Jigsaw, Think Pair Share and Confensional Types to Improve the Learning Outcomes of Vocational School Students in PAI Subjects Based on Middle School Origin and Mts - Ahmad Subarna; Wati Susilawati; Adam Malik (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study aims to determine; (1) The effect of applying the jigsaw type cooperative learning model, think pair share and conventional on Islamic Religious Education subjects; (2) Student learning outcomes based on school origin factors; (3) Interaction between learning models and school origin factors. The approach taken in this study used a quantitative approach with a quasi-experimental method. The population of this research is class X students of SMK Negeri 10 Bandung. The data analysis technique used in this research is two-way ANOVA analysis. The results showed that; (1) There are differences in student learning outcomes in PAI subjects based on jigsaw, think pair share and conventional cooperative learning models; (2) There are no differences in student learning outcomes based on school origin factors; (3) There is no interaction between learning models and school origin factors in determining student learning outcomes. Cooperative learning models of jigsaw type, think pair share and conventional applied have an influence on student learning outcomes based on school origin in Islamic Religious Education subjects.